2014
DOI: 10.1371/journal.pone.0102442
|View full text |Cite
|
Sign up to set email alerts
|

P-Glycoprotein Mediated Efflux Limits the Transport of the Novel Anti-Parkinson's Disease Candidate Drug FLZ across the Physiological and PD Pathological In Vitro BBB Models

Abstract: FLZ, a novel anti-Parkinson's disease (PD) candidate drug, has shown poor blood-brain barrier (BBB) penetration based on the pharmacokinetic study using rat brain. P-glycoprotein (P-gp) and breast cancer resistance protein (BCRP) are two important transporters obstructing substrates entry into the CNS as well as in relation to PD neuropathology. However, it is unclear whether P-gp and BCRP are involved in low BBB permeability of FLZ and what the differences of FLZ brain penetration are between normal and Parki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 33 publications
0
28
0
1
Order By: Relevance
“…Transport studies were also performed, where only P-gp blocker effectively inhibited the efflux of FLZ. Thus, from this study it is possible to conclude that P-gp is the main responsible for poor brain penetration of FLZ and low BBB permeability (Liu et al, 2014).…”
Section: Drug Efflux Transportersmentioning
confidence: 55%
“…Transport studies were also performed, where only P-gp blocker effectively inhibited the efflux of FLZ. Thus, from this study it is possible to conclude that P-gp is the main responsible for poor brain penetration of FLZ and low BBB permeability (Liu et al, 2014).…”
Section: Drug Efflux Transportersmentioning
confidence: 55%
“…In addition, it was observed that in vitro BBB model facilitates the manipulation of some parameters that affects the barrier such as aglycemia, hypoxia, among others [32]. For decades, two-dimensional or three-dimensional in vitro models of BBB have been developed by cultivating either as a monolayer or in cocultivation with mouse brain microvascular endothelial cells and murine or human endothelial cells with pericytes or astrocytes or glial tissue among others in a way that mimics the barrier under physiological or pathological conditions such as Alzheimer's and Parkinson's diseases or stroke [33][34][35][36][37]. Models of BBB based on stem cells are also reported in the literature [38,39].…”
Section: In Vitro Approaches To Study Nps' Transport Through the Bbbmentioning
confidence: 99%
“…[25][26][27] Our previous study investigated the cellular transport of nimesulide and the para-methoxy substituted analog 1d across Caco-2 cells, which provide a valid surrogate model for the BBB efflux behavior of pharmaceutical molecules. 28 This study indicated that neither nimesulide nor 1d were P-gp substrates in vitro.…”
Section: In Vitro Transport Studies In Caco-2 Cellsmentioning
confidence: 99%